The Effect of Service Quality, Corporate Image, and Price Perceived in Creating Customer Satisfaction and Loyalty on Education Business - Slamet Heri Winarno; Aloysius Rangga Aditya Nalendra; Bryan Givan (Esensi: Jurnal Bisnis dan Manajemen, 2020)
Competition in business services, especially education services show a trend that increasingly tight nowadays. Each school is required to be able to create a level of satisfaction and loyalty for its service users. This study was conducted to determine the effect of service quality, corporate image and price perception in creating customer satisfaction and loyalty. In this study using 173 respondents as a sample by using the method of saturated sampling. This research is a quantitative research using the observation method, interview, and spreading of the questionnaire. The analysis technique used is Structural Equation Modeling (SEM) with the path diagram. Variables used include quality of service (X1), corporate image (X2), price perception (X3), customer satisfaction (Y1) and customer loyalty (Y2). The results showed that customer satisfaction is influenced by corporate image and price perception of 18.4% while customer loyalty is influenced by price perception and customer satisfaction of 60.5%. This suggests that service quality is not always a decisive factor in customer satisfaction and loyalty.